2023
DOI: 10.3390/ijerph20227087
|View full text |Cite
|
Sign up to set email alerts
|

The Promotion of Mental Health and Prevention of First-Episode Psychosis: A Pilot and Feasibility Non-Randomised Clinical Trial

Lucia Santonja Ayuso,
Antonio Ruiz-Hontangas,
José Javier González Cervantes
et al.

Abstract: Background: Mental-health-related stigma prevents active help seeking and therefore early therapeutic approaches and the recovery of functionality. National and international agencies recommend the implementation of prevention and mental health promotion programs that support the elimination of stigma in the classroom, since most mental health problems usually start in the adolescent stage. In view of the evidence that teachers present stigmatizing attitudes towards mental health, it has been considered as con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…For example, a recent systematic review of the literature on family support programs has demonstrated that these programs are effective in improving both caregivers' and children's mental health [46]. Similarly, the positive impact of the workshop found on teachers' confidence and importance to tackle difficult behaviours in adolescents corroborates previous findings on the efficacy of teachers' training to improve mental health literacy, reduce stigma, and increase confidence to offer help to students [47,48].…”
Section: Discussionsupporting
confidence: 70%
“…For example, a recent systematic review of the literature on family support programs has demonstrated that these programs are effective in improving both caregivers' and children's mental health [46]. Similarly, the positive impact of the workshop found on teachers' confidence and importance to tackle difficult behaviours in adolescents corroborates previous findings on the efficacy of teachers' training to improve mental health literacy, reduce stigma, and increase confidence to offer help to students [47,48].…”
Section: Discussionsupporting
confidence: 70%